Pengembangan Media Pembelajaran Matematika Berbasis Adobe Animate Materi Bangun Ruang Sisi Datar dengan Pendekatan Etnomatematika Pada Siswa Kelas IX - Wardana, Jaka Wisnu; Buchori, Achmad; Purwosetiyono, FX Didik (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
This study aims to develop Adobe Animate based mathematics learning media on flat sided geometry with an ethnomathematical approach. This type of research is Research and Development using the ADDIE development model which includes 4 steps, namely Analysis, Design, Development and Implementation. The research subjects were 29 students of class IX A as the experimental class. Media development using Adobe Animate software. The results of this study indicate that the media is declared feasible based on material expert validation with a percentage of feasibility and media expert validation of 94% and material validation of 82%. Furthermore, revisions were made based on input from the validator, so that the mathematics learning media based on Adobe Animate on the flat sided geometry material with an ethnomathematical approach was declared feasible. And also searched for student responses to the developed media, and obtained student responses of 94.77% with a very good category.